Peningkatan Keterampilan Membaca Cerpen dengan Metode P2R dan Model Berpikir-Berbasangan-Berbagi pada Siswa Kelas IX SMP Negeri 1 Poto Tano Tahun Pelajaran 2019/2020 - Seni Hadiawati (Yayasan Pembina Lembaga Pendidikan (YPLP) PGRI Kabupaten Sumbawa Barat - NTB - Indonesia, 2020)
Short story reading skills of grade IX students of SMP Negeri 1 Poto Tano are still low. This is because students find it difficult to retell the contents of short stories and find intrinsic elements in short stories. This is due to the use of approaches and learning media that are less interesting and boring. In addition, the teacher has not been intensive to guide students in learning to read short stories. Based on the results of this action research shows that using the P2R method and thinking-pair-sharing models in reading short stories in class IX students with 100% completeness, thus reading short stories with the P2R method and thinking-pair-sharing models in class IX students of SMP Negeri 1 Poto Tano is good.